Traditional Chinese Medicine of Angelicae Pubescentis Radix: A Review of Phytochemistry, Pharmacology and Pharmacokinetics - Lu, Yaqi; Wu, Hongwei; Yu, Xiankuo; Zhang, Xiao; Luo, Hanyan; Tang, Liying; Wang, Zhuju (Frontiers in Pharmacology, 2020)
Angelicae Pubescentis Radix (APR) is a widely used antirheumatic Chinese medicinal herb known as “Duhuo”. It has the effects of dispelling wind and removing dampness, diffuse impediment and relieve pain, and mainly treating rheumatic arthritis with pain in the lower back and knees, and headache. Up to present, a variety of chemical constituents have been reported from the plants of this traditional Chinese medicine (TCM), mostly coumarins and volatile oil. Numerous studies have shown that the extracts and compounds isolated from APR show an effective analgesic and anti-inflammatory actions, also including central nervous system effects, cardiovascular system effects, effects on the diastolic trachea, and deworming activity. In addition, we also present and discuss the botany, traditional medicinal use, pharmacokinetics, toxicity, quality control, future trends and prospects of APR. All this information suggest that future research of APR should be supplemented in the area of pharmacology and toxicology to provide further insight on the clinical use and quality control.